Market imperfections and child labor - Christelle Dumas (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
There is some indirect evidence that child labor is affected by market imperfections. This paper provides a theoretical model to discuss the effect of improvements on the labor market, when households cannot rely on neither the land nor the credit markets. The predictions differ by land ownership: landless or large landowners should decrease child labor when labor market imperfections decrease. Households who had chosen not to supply any labor on the wage market (households with intermediate-upper land levels) remain unaffected and households who combine farm work with wage work (households with intermediate-lower land levels) may either increase or decrease their child labor use. We use Malagasy data to estimate the relation between child labor and various measures of markets imperfections. We match those data with a municipality census so as to control for a large set of village characteristics. We find that on average market imperfections (labor but also land and credit) do indeed increase child labor and obtain heterogenous effects by land ownership that are consistent with the theoretical model. The results point to the fact that an improvement of markets competitiveness should decrease child labor (and even the more so for labor markets), which provides an alternative policy to fight against child labor.
Keywords: O12; O13; O15; J13; J43; 330; Child labor; Market imperfections; Land; Labor; Credit; Madagascar